Stop and Frisk Redux: Analysis of Racial Bias in New York City - Gutman, Abraham (2016)
Stop and Frisk is a policing practice used commonly in NYC. For some, equal arrest rates for non-white and white pedestrians indicate no racial bias. I challenge that conclusion and argue that heterogeneity masks lower arrest rates of non-white pedestrians. I conclude that Stop and Frisk is an uneven policing practice that carries racial bias